2014
DOI: 10.1001/jamainternmed.2014.3293
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia After Antimicrobial Drug Prescription for Older Patients Using Sulfonylureas

Abstract: IMPORTANCE Certain antimicrobial drugs interact with sulfonylureas to increase the risk of hypoglycemia.OBJECTIVE To determine the risk of hypoglycemia and associated costs in older patients prescribed glipizide or glyburide who fill a prescription for an antimicrobial drug. DESIGN, SETTING, AND PARTICIPANTSThis was a retrospective cohort study of Texas Medicare claims from 2006 to 2009 for patients 66 years or older who were prescribed glipizide or glyburide and who also filled a prescription for 1 of the 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 43 publications
3
50
1
2
Order By: Relevance
“…This is even more important, when drugs are used temporarily, for example in case of antimicrobial treatment. Many antibiotic drugs affect hepatic enzyme activity and thus substantially increase hypoglycemic risk with SU, and are associated with higher morbidity and increased costs [Parekh et al 2014]. Thus, interactions due to CYP2C9 inhibition play a crucial role in the treatment with SUs.…”
Section: Susmentioning
confidence: 99%
See 2 more Smart Citations
“…This is even more important, when drugs are used temporarily, for example in case of antimicrobial treatment. Many antibiotic drugs affect hepatic enzyme activity and thus substantially increase hypoglycemic risk with SU, and are associated with higher morbidity and increased costs [Parekh et al 2014]. Thus, interactions due to CYP2C9 inhibition play a crucial role in the treatment with SUs.…”
Section: Susmentioning
confidence: 99%
“…Beta blockers can mask the early warning symptoms of hypoglycemia; however, later studies have shown that these effects may be less prominent with newer beta-1 selective drugs [Shorr et al 1997]. As mentioned earlier, many antimicrobials present a high interaction risk with antidiabetics, especially with Sulfonylureas [Tirkkonen et al 2010, Parekh et al 2014. Interactions with antimicrobials are clinically most relevant because adverse effects take place most often whenever a drug is added or removed [Patsalos et al 2003], and antimicrobials are usually taken temporarily.…”
Section: Drugs Affecting the Efficacy Of Antidiabetic Agents In Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoglycaemia induced by polymedication can be explained, in part, by the increased risk of drug interactions. For example, co-prescription of sulfonylureas and quinolones or sulfamethoxazole–trimethoprim were associated with hypoglycaemia in elderly patients,36 as well as non-cardioselective β-blockers by masking hypoglycaemia symptoms during insulin therapy 37. In our cohort, no specific interaction was found to be associated with hypoglycaemia, explained in part by the broad range of different drugs and thus reducing statistical power.…”
Section: Discussionmentioning
confidence: 58%
“…A retrospective cohort study of Texas Medicare claims from 2006 and 2009 for older patients who were co-prescribed sulfanylureas with one of the most commonly used antimicrobials assessed the risk of hospitalization or emergency department visit owing to hypoglycaemia within 14 days of antimicrobial exposure. Multivariate analyses showed that the risk of hypoglycaemia varied according to the type of antimicrobial administered and was higher with clarithromycin (OR 3.96; 95% CI 2.42-6.49), levofloxacin (OR 2.60; 95% CI 2.18-3.10), trimethoprim/sulfamethoxazole (OR 2.56; 95% CI 2.12-3.10), metronidazole (OR 2.11; 95% CI 1.28-3.47) and ciprofloxacin (OR 1.62; 95% CI 1.33-1.97) compared with a panel of non-interacting antimicrobials (amoxicillin, azithromycin, cefdinir, cefuroxime, cephalexin, clindamycin, doxycicline, nitrofurantoin and penicillin V) [34 ]. Likewise, a population-based inception cohort study assessed the risk of hospitalization or emergency department visit owing to dysglycemia within 30 days of antimicrobial exposure among diabetic outpatients who were new users of fluoroquinolones, macrolides or cephalosporins.…”
Section: Antimicrobial Treatment Of Bacterial Infections In Frail Eldmentioning
confidence: 99%